(untitled) (Revista Contexto & Educação, 2021)
This paper aims to verify the perception of a group of teachers and students regarding the limits and possibilities of carrying out an integrator project in an institution of Professional and Technological Education, in an attempt to implement the integrated curriculum. Participative research was used for the methodology. As a result, we found that the integrator project collaborates significantly in the teaching and learning process, including the proposed theme, which is, indigenous corporealities, as it sought integration between the various areas of knowledge. As positive points we point out the approximation of the disciplines, the valorization of cultural diversity, the accomplishment of interdisciplinary activities and the reduction of the amount of evaluative activities. As negative points, we have little time to carry out the proposal, the lack of adequate spaces for its preparation and the lack of commitment of some teachers and students. The development of this research showed us that the integrator project is a valuable tool for the implementation of the integrated curriculum in the school environment, especially in Professional and Technological Education. However, its success is conditioned to a greater articulation of efforts between public managers, school managers, teachers and students.